Embryonal rhabdomyosarcoma in a patient with a germline CBL pathogenic variant - Ji, Jianling (Cancer Genet, 2018)
Germline pathogenic variants in CBL are associated with an autosomal dominant RASopathy and an increased risk for malignancies, particularly juvenile myelomonocytic leukemia. Herein, we describe a patient with clinical features of a Noonan-spectrum disorder who developed embryonal rhabdomyosarcoma of the bladder at age two years. Tumor analysis using the OncoKids(®) cancer panel revealed a CBL pathogenic variant: NM_005188.3:c.1100A>C (p.Gln367Pro). Sanger sequencing of peripheral blood DNA confirmed a de novo heterozygous germline variant. This is the first report of embryonal rhabdomyosarcoma in association with a germline CBL pathogenic variant, further broadening the CBL cancer predisposition spectrum.